MORPHOLOGY OF BATAAFSE PETROLEUM MAATSCHAPPIJ BECOME PERTAMINA SEMARANG AS A CONSERVATION EFFORT - Paramtopo, Dewanggo Haryo; Rukayah, R Siti (Border: Jurnal Arsitektur, 2023)
Conservation can be used as a process of maintaining a place as an effort to preserve cultural values. Conservation includes maintenance and may be appropriate to the situation including preservation, restoration, reconstruction and adaptation. Conservation buildings also have architectural, aesthetic, historical, documentary, archaeological, economic and social values. The Bataafse Petroleum Maatschappij Cultural Heritage Building, which is currently a Pertamina building, is a cultural heritage building with registration number 92. This company is the forerunner of Pertamina Indonesia. There was a change from The Bataafse Petroleum Maatschappij 1920 to PT. Pertamina Persero has gone through five name changes, namely PN. Permina 1957, PN. Pertamina 1961, PN. Pertamina, Pertamina 1971, and the last change to PT. Pertamina Persero in 2003 the change of name was related to a change in function so that from the change in function the aim of the research was to analyze the morphology of the cultural heritage building of the oil industry building to become Pertamina's office as a conservation effort with research limitations in 1920 and 2023. The research method carried out was qualitative with descriptive method. Because the method describes the actual phenomenon in the field and then analyzes it. The qualitative research process develops dynamically according to the information obtained and the conditions of the research subjects.